ANALISIS VARIABEL MAKRO DAN RASIO KEUANGAN TERHADAP KREDIT BERMASALAH - Muhammad Rahmadi Yusuf; Fakhruddin Fakhruddin (Syiah Kuala University, 2016)
The research aims to analyze the impact of the macro variables and variable financial ratios to Non Performing Loan analysis method used was Ordinary Least Square ( OLS ) using quarterly data from 2003: 1 to 2014: 4 . The results showed that the variables of Exchange Rate ,the Gross Domestic Product, and Loan to Deposit Ratio (LDR) has a negative impact significantly on the NPLs, variable lending rates and Capital Adequacy Ratio (CAR) has a significant positive effect, simultaneously and together variable Non Performing Loan effect significant. Variable credit rate has a strong influence which led to an increase in NPLs . For further research, it is advisable to increase the number of variables that will be studied in order to determine what variables that influenced the Non Performing Loan.